2010
DOI: 10.1038/cgt.2010.12
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced growth inhibition of metastatic lung tumors by intravenous injection of ATRA-cationic liposome/IL-12 pDNA complexes in mice

Abstract: Interleukin 12 (IL-12) is a proinflammatory cytokine with antitumor activity. All-trans-retinoic acid (ATRA) exerts antitumor effects by regulating a variety of gene expressions, including tumor necrosis factor receptor 1 (TNFR1), increases the number of TNFR1 and potentiates TNF-a-induced apoptosis in cancer cells. In this study, ATRA-incorporated cationic liposome (ATRA-cationic liposome)/ IL-12 plasmid DNA (pDNA) complexes were prepared to improve therapeutic efficacy of cationic liposome/IL-12 pDNA complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…Generally, in the absence of ligands, RARs are associated with co-repressors to inhibit transcription, while liganded RARs recruit co-activators to activate transcription [32]. Clinical applications of AtRA have had some success in the treatment of human diseases such as cancer, psoriasis, leukemia, restenosis and plaque formation [31,33]. Nevertheless, the precise mechanism by which RARs function to control p21 and thus govern cell proliferation is still not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, in the absence of ligands, RARs are associated with co-repressors to inhibit transcription, while liganded RARs recruit co-activators to activate transcription [32]. Clinical applications of AtRA have had some success in the treatment of human diseases such as cancer, psoriasis, leukemia, restenosis and plaque formation [31,33]. Nevertheless, the precise mechanism by which RARs function to control p21 and thus govern cell proliferation is still not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…RARs are now considered to be an attractive research target for treatment of VSMC proliferation disease (28,29). Clinical applications of ATRA have successfully been applied in human diseases such as leukemia, cancer, restenosis, and plaque formation (29,30). Despite these advances, the mechanisms by which ATRA functions to induce Klf4 transcription are still largely unknown.…”
mentioning
confidence: 99%
“…Antimetastatic effects of RA against mouse pulmonary metastatic model have been investigated by several researchers. 25,27 We also demonstrated the antimetastatic activity of RA-incorporated nanoparticles using mouse pulmonary metastatic model of CT26 cells, as shown in Figure 7. Suzuki et al reported that RA-encapsulated cationic liposome suppressed pulmonary metastasis of tumor cells.…”
Section: Discussionmentioning
confidence: 67%
“…25,26 CT26 cells were administered into the tail vein of BALb/C mice (1 Ɨ 10 5 cells/0.2 mL Hank's balanced salt solution). RA was dissolved in 5% HCO-60 (Nicco Chemicals, Tokyo, Japan) solution, and RAincorporated nanoparticles were administered via the tail vein (RA dose 5 mg/kg) at day 3 after tumor inoculation.…”
Section: In Vivo Ct26 Pulmonary Metastasis Modelmentioning
confidence: 99%